Cluster analysis allowed to identify antifungal drugs that retain efficacy against Candida albicans isolated from patients with inflammatory diseases of the soft tissues of the maxillofacial area - Faustova, Mariia; Dobrovolskyi, Volodymyr; Loban’, Galina; Bereza, Yevhenii; Kotelnikova, Aleksandra; Dobrovolskyi, Oleksandr (Frontiers in Oral Health, 2024)
Physicians are increasingly prescribing antifungal drugs empirically to treat hospital-acquired infections quickly. This makes it obvious that fungal infections require more attention and systematic monitoring of resistance among them. The aim of the study was to identify antifungal drugs that retain their efficacy against C. albicans isolates. There were 17 clinical isolates of Candida albicans obtained from patients and tested for susceptibility to antifungal drugs using the standard double dilution method. Amphotericin B, fluconazole, itraconazole, micafungin, and posaconazole were used in the study. To determine the groups of antimycotics to which the studied microorganisms retain sensitivity, a hierarchical cluster analysis was performed using the Ward's method. The tested representatives of the genus Candida showed the lowest sensitivity to fluconazole. The efficacy of amphotericin B and itraconazole was almost at the same level. In turn, micafungin and posaconazole showed the best results against C. albicans isolates. Ward's cluster analysis combined the results of C. albicans susceptibility to fluconazole, micafungin and itraconazole by the highest mathematical similarity. Amphotericin B and posaconazole were combined into one cluster due to their better efficacy against Candida albicans isolates.